General public´s approach to health care from the perspective of health professionals - Hudáčková, Andrea; Chloubová, Iva; Dolák, František (STEF92 Technology Ltd., 2018)
The aim of the study was to identify the professional public`s opinion of general public`s health literacy and approach to their own health. A quantitative method using a non-standardized questionnaire was chosen to meet this aim. This questionnaire was based on the standardized questionnaire called The HLS-EU-47 of the HLSEU Consortium for the European Health Literacy Survey (HLS-EU), which is designed for the identification of health literacy. The questionnaire contained 38 questions arranged in individual areas and constructed in a way enabling to identify the healthcare professionals` opinions of the general public`s approach to primary prevention and to identify the general public`s health literacy. The choice of the sample was a quota choice, i.e., the respondents were employed by healthcare institutions of the South Bohemian Region, CR. It was a condition that the selected institution was involved in primary, secondary and tertiary prevention. 166 respondents participated in the study. The results were processed by SASD software. Results: The health professionals mostly agree on the fact that health care information is usually accessible for general public; however, patients are not always able to deal with this information. For example, patients are able to obtain information of the protection from diseases, and health promoting activities but find difficult to assess whether their health and wellness are influenced by their life styles. In the health professionals` opinion, the general public do not quite realize the necessity of general preventive examinations. On the other hand, they realize this necessity in the case of specialist examinations. A deeper statistic analysis did not find any significant correlations between the opinions of medical and non-medical professionals.
Přístup laické veřejnosti ke zdravotní péči z pohledu zdravotnických pracovníků
Keywords: General Public; Primary Prevention; General Preventive Examinations; Health Professionals; Laická veřejnost, Primární prevence, Primární preventivní péče, Zdravotničtí pracovních